Internal and External Quality in the Framework of Educational Quality Assurance: A Conceptual Analysis of the Quality of Educational Institutions - Masniatul Ilmiah; Muallimin Muallimin; Khoirul Anwar (Penerbit Hellow Pustaka, 2026)
Improving educational quality has become a significant issue in the management of educational institutions in response to increasing demands for accountability, transparency, and global competitiveness. Educational institutions are not only expected to produce competent graduates but also to establish sustainable quality management systems. In this context, the concepts of internal quality and external quality represent essential components within the framework of educational quality assurance. This study aims to conceptually examine the relationship between internal and external quality in the management of educational institutions and to address how these two dimensions contribute to improving institutional quality. This research employs a literature review method by collecting scholarly sources from the Google Scholar database using the Publish or Perish (PoP) software. The literature search used the keywords “internal quality,” “external quality,” and “educational quality assurance.” The selection process involved screening and eligibility stages, starting from approximately 47 initial articles, which were refined to 17 relevant articles for analysis. The findings reveal that the literature highlights two major themes: strengthening internal quality assurance systems through effective management of educational resources and achieving external quality recognition through accreditation mechanisms, public trust, and graduate competitiveness. The integration of these two quality dimensions plays a crucial role in establishing an accountable and sustainable education system. Future research is recommended to explore empirical implementations of the relationship between internal and external quality across different types of educational institutions.